(untitled) (Eurasian Scientific Herald, 2022)
It is about the relations between the fraternal peoples living in the land of Turkestan, the traditions of each other. The world recognizes the customs of each nation. Examples include throwing tomatoes in Spain, escorting a coffin to a funeral in Ghana, making an ice statue in Japan, swimming in ice in cold weather in Russia, and so on. The Karakalpak people also have their own traditions. In this article, you will see the interdependence of fraternal peoples.